PEER ASSESSMENT AND SELF ASSESSMENT FOR EVALUATING STUDENTS’ PERFORMANCE IN REDOX REACTION LABORATORY - Siswaningsih, Wiwi; Nahadi, Nahadi; Tresna, Finna Citra (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Assesment is an inseparable part of an educational program. The aim of this research was to develop peer assessment and self-assessment for evaluating students’ performance in redox reaction laboratory. This study was conducted in one of high school in Bandung with 42 students as its sample. Peer assessment and self-assessment instrument were found to be valid dan reliable. Implementation stage further showed the potency of this instrument as students performance assessment in which peer and self-assessment was highly correlated with expert assesment results.